Environmental Health Risk Assessment (EHRA) to Achieve the Target of Universal Access 2020 on Domestic Waste Water Sector in Blitar Districts - Edy Santosa, Florianus Rooslan (International Journal of Integrated Engineering, 2019)
Development of urban city is commonly followed by steady growth of economic condition, population density, and negative impact of environmental condition. Reduction quality of environmental condition stimulates the occurrence of environmental degradation within society. Low quality of waste water system, management of garbage, limitation of green areas, and low concern of society toward climate change are example of environmental issues that need to be solved by the government as soon as possible. The succession in achieving aims of Millennium Development Goals (MDGs) is continued by Sustainable Development Goals (SDGs) program from 2015 to 2030. SDGs have numerous action plans in achieving its goals for instance Environmental Health Risk Assessment (EHRA) for waste water system in Blitar District. Research methods that use in the present study are as follow (i) Field study named Environmental Health Risk Assessment (EHRA), and (ii) data collection, entry data, data cleaning, data processing and data analysis. The present study concludes numerous results achievement for waste water access are follow: very high (180 villages or 72.58 %), high (26 villages or 10.48 %), medium (28 villages or 11.29 %), low (14 villages or 5.65 %). It can be concluded that the achievement for SDGs for waste water system has been achieved.